Exploiting inter-reference time characteristic of Web cache workload for web cache replacement design - Sediyono, Agung (2009)
Caching objects in Internet environment is aimed to reduce bandwidth consumption and increase the response time of system in term of user perception.Researcher believes that the performance of web cache is dependent on user access behavior.Therefore, many studies on workload of the internet web cache have been conducted.However, in the web cache environment, the study in inter-reference time of the successive requests is rarely.This paper tries to explore the characteristic of workload of the internet web cache, especially on the inter reference time (IRT).Based on the correlation test and trend analysis, it can be concluded that IRT is reasonable to be applied as a metric of web cache replacement policy.